Pengaruh Kualitas Pelayanan dan Fasilitas Keamanan Terhadap Kepuasan Pengguna Jasa di UPBU Rahada Oesman Ketapang - Friska Nia Audina (Jurnal Multidisiplin Madani, 2022)
This study intends to determine the effect of service quality and security facilities on service user satisfaction at UPBU Rahadi Oesman Ketapang. Quantitative method is the method applied in this research. The population of this study is all service users or passengers at UPBU Rahadi Oesman Ketapang in 2020, totaling 138,719 and a sample of 100 respondents. Sources of data used are secondary data in the form of documentation and primary data obtained directly through a questionnaire. The results of the analysis of the T test data obtained that service quality has a positive and significant effect on user satisfaction and security facilities have a positive and significant effect on user satisfaction. Analysis of the F test data obtained that the quality of service and security facilities together have a positive and significant effect on service user satisfaction at UPBU Rahadi Oesman Ketapang.